2003
DOI: 10.1088/0953-8984/15/30/311
|View full text |Cite
|
Sign up to set email alerts
|

Indium–carbon pairs in germanium

Abstract: The interactions of carbon with the probe nucleus 111In have been studied in germanium using the perturbed angular correlation method, which has the ability to detect the microscopic environments of the probe atom by means of the interaction of the nuclear moments of the probe with the surrounding electromagnetic fields. At high dose carbon implantation in germanium two complexes have been identified by their unique quadrupole interaction frequencies. An interaction frequency of νQ1 = 207(1) MHz (η = 0.16(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…Nevertheless, the identical frequency ν Q = 348 MHz is observed in two different compounds. The strength of the observed EFGs is similar to impurity-In pairs in semiconductors [10]. We propose, that the 111 In probe-sitting on the A-site-catches an interstitial carbon atom.…”
Section: Discussionsupporting
confidence: 63%
“…Nevertheless, the identical frequency ν Q = 348 MHz is observed in two different compounds. The strength of the observed EFGs is similar to impurity-In pairs in semiconductors [10]. We propose, that the 111 In probe-sitting on the A-site-catches an interstitial carbon atom.…”
Section: Discussionsupporting
confidence: 63%
“…This sensitivity is advantageous for discriminating the presence of intrinsic and extrinsic defects in semiconductors, which is in general a basic problem in defect studies. Extensive PAC data are available on such measurements in semiconductors, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] which can be summarized as follows:…”
Section: Hyperfine Interactionsmentioning
confidence: 99%
“…On the basis of unique and distinct EFG, indiumdopant pairs in silicon, [8][9][10] and indium-vacancy, indium-interstitial, and indium-carbon pairs in germanium 11,12 were identified using PAC technique with 111 In probe atoms. The formation of similar defect complexes was also observed in II-VI semiconductors CdTe, ZnTe, ZnSe, and Hg 1Àx Cd x Te.…”
Section: Hyperfine Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-doping C with In is one of the most promising approaches to meet such a requirement. It has been reported that in both Si [3,[11][12][13] and Ge, [14][15][16] enhancement of In electrical activation was realized by C co-doping. Above-equilibrium solid solubility was attained in both substrates as a consequence of C-In pair formation that suppressed In precipitation.…”
mentioning
confidence: 99%